2020
DOI: 10.1017/s136898002000498x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of emotional (depression) and behavioural (nutritional, physical activity and sleep) status of Turkish adults during the COVID-19 pandemic period

Abstract: Objective: To evaluate emotional (depression) and behavioural (nutritional behaviours, physical activity status and sleep patterns) of Turkish adult individuals during the COVID-19 pandemic period. Design: Cross-sectional online survey. The participants filled out a questionnaire (developed by using Google Forms) that contained descriptive characteristics, nutritional behaviours, sleep patterns, physical activity status, anthropometric measurements, COVID-19-related level of knowledge an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
(57 reference statements)
1
6
0
3
Order By: Relevance
“…In this study, a decrease in physical activity; an increase in sleep duration, consumption of convenience foods, and consumption of delivered foods; a decrease in alcohol consumption and smoking; a decrease in the number of social meetings; and a decrease in the use of public transportation were confirmed to be due to COVID-19–related lifestyle changes. These findings are in accordance with those from previous studies that demonstrated that owing to the spread of COVID-19 and the effects of social (i.e., physical) distancing, individuals demonstrated a decrease in physical activity; an increase in sleep duration; an increase in the consumption of convenience foods (including delivered foods); a decrease in the number of social meetings; and a decrease in the use of public transportation [ 16 - 19 ]. These lifestyle changes can have far-reaching consequences for individuals’ physical and psychological well-being.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, a decrease in physical activity; an increase in sleep duration, consumption of convenience foods, and consumption of delivered foods; a decrease in alcohol consumption and smoking; a decrease in the number of social meetings; and a decrease in the use of public transportation were confirmed to be due to COVID-19–related lifestyle changes. These findings are in accordance with those from previous studies that demonstrated that owing to the spread of COVID-19 and the effects of social (i.e., physical) distancing, individuals demonstrated a decrease in physical activity; an increase in sleep duration; an increase in the consumption of convenience foods (including delivered foods); a decrease in the number of social meetings; and a decrease in the use of public transportation [ 16 - 19 ]. These lifestyle changes can have far-reaching consequences for individuals’ physical and psychological well-being.…”
Section: Discussionsupporting
confidence: 92%
“…There were 64 studies included within the review [ 18 , 20 , 21 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , …”
Section: Resultsunclassified
“…Specific populations included elite athletes [ 43 ], post-bariatric patients [ 44 ], pregnant women [ 45 ], participants with depression [ 82 ], and children with autism [ 27 ], attention deficit hyperactivity disorder (ADHD, [ 28 ]), and obesity [ 29 ]. Finally, 25 studies (37.5%) were conducted in European countries (Austria, France, Germany, Italy, Poland, Scotland, Spain, and the United Kingdom; [ 27 , 29 , 30 , 31 , 32 , 42 , 43 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]), 18 (28.1%) in Asia (Australia, Bangladesh, China, India, Jordan, Kuwait, Turkey and the United Arab Emirates; [ 20 , 21 , 28 , 33 , 34 , 35 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]), 12 (18.8%) in North America (Canada and United States; [ 18 , 36 ,…”
Section: Resultsmentioning
confidence: 99%
“…These studies, which covered a relatively short period of the pandemic, stated that small changes in body weight may become permanent, and result in significant weight gain over time [ 45 46 47 ]. In 2 studies in Turkey that were conducted at the beginning of the pandemic, it was observed that the rate of participants who stated that their body weight increased (35.0%; 38.4%) and did not change (36.0%; 48.6%) was higher than those who stated that they lost weight [ 38 48 ]. In the present study, which was planned to determine the long-term effects of the pandemic, it was found that 58.96% of the participants gained weight, and 30.74% lost weight at the end of 1 yr of the pandemic.…”
Section: Discussionmentioning
confidence: 99%